Cameroon: Flawed Decentralization and the Politics Of Identity in the Urban Space (Global Journal of Human-Social Science, 2012)
Urban governance policies in Cameroon within the past two decades of political and economic liberalization have witnessed significant administrative and political setbacks While the government of Cameroon tacitly embraced decentralization as a viable administrative and political strategy for improving the management of cities the process has been stalled by excessive state interventionism This paper draws on the decentralization experience of the coastal city of Limbe in the southwest region of Cameroon to analyze the emerging trajectories of conflict embedded in the current decentralization drive of city governance Based on interviews of some municipal officials conducted in May and June 2011 this paper makes the case that the current urban governance crisis in Cameroon is traceable largely to the weak political impulse of central government to effectively relinquish its traditional grip on power at all levels of society This partly explains why cities in Cameroon have failed to deliver expected services to their clientele the population on a regular and efficient manner
Keywords: Economic liberalization; effectively relinquish